Development of an automated greenhouse with control system - Wong, Adam Yoon Khang; Abdul Rahman, Ahmad Idil; Mohamat Gani, Johar Akbar; Mohd Azmi, Hanis Saadah (Asian Research Publishing Network (ARPN), 2025)
This study introduces an innovative approach to greenhouse farming by developing an automated greenhouse with a control system, utilizing the Arduino Uno and Nvidia Jetson Nano. Acknowledging the limitations of traditional methods reliant on manual labour, the automated greenhouse integrates sensors and control systems to regulate temperature, humidity, soil moisture, water level, and light. By automating processes such as irrigation and ventilation, the system optimizes plant growth and yield while reducing energy consumption and labour costs. The project's primary objective is to revolutionize crop cultivation by creating a precise environmental control system and utilizing data analysis tools. The study envisions a cloud-based platform for real-time monitoring and control, emphasizing the potential to enhance efficiency and sustainability in greenhouse farming. Through performance assessments and a focus on scalability for commercial use, the project aims to achieve significant results in transforming agricultural practices. Overall, the utilization of Arduino Uno and Jetson Nano, combined with the project's objectives and achievements, underscores its importance in advancing greenhouse farming towards greater efficiency and sustainability.